Views of pregnant women and clinicians regarding discussion of exposure to phthalate plasticizers - Sharma, Sapna (BioMed Central, 2014)
OBJECTIVE: This study explores the views of pregnant women and clinicians regarding discussion of exposure to phthalate plasticizers during pregnancy, subsequent to the 2011 Health Canada ban of certain phthalates at a concentration greater than 1000 mg/kg in baby toys. This occurred with no regulation of products to which pregnant women are exposed, such as food packaging and cosmetics. METHODS: Pregnant women, physicians and midwives were recruited through posters and pamphlets in prenatal clinics in Southwestern Ontario for a semi-structured interview. All interviews were audiotaped, transcribed, and subjected to rigorous qualitative analysis through a grounded theory approach, supported by NVIVO™ software. Themes emerged from line by line, open, and axial coding in an iterative manner. RESULTS: Theoretical sufficiency was reached after 23 pregnant women and 11 clinicians had been interviewed. The themes (and subthemes from which they arose) were: Theme I-Information Provision (IA-Sources of Information, IB-Standardization, IC-Constraints, ID-Role of Government); Theme II-Risk (IIA-Significant Risk, IIB-Perceived Relevance, IIC-Reconciliation); and Theme III- Factors Influencing Level of Concern (IIIA-Current Knowledge, IIIB-Demographic Factors). CONCLUSION: To respond to the increasing media and research attention regarding risk of phthalates to women, and pregnant women in particular, national professional organizations should provide patient information. This could include pamphlets on what a pregnant woman should know about phthalates and how they can be avoided, as well as information to clinicians to facilitate this discussion.